University Students’ Experiences with ChatGPT as an English Learning Partner: A Qualitative Study - Azizi Fauziah, Husnul; Armin, Diah Safithri (Indo-MathEdu Intellectuals Journal, 2026)
The use of artificial intelligence in English language learning in higher education continues to increase, but understanding of students' perceptions of ChatGPT as an academic learning partner remains limited. Therefore, this study aims to explore students' perceptions of the use of ChatGPT as an English learning partner and its role in supporting independent and academic learning. This study used a qualitative approach with a descriptive design. Data were collected through open-ended questionnaires and semi-structured interviews with undergraduate students who had experience using ChatGPT in English learning. Data were analyzed using thematic analysis techniques to identify patterns and meanings within students' experiences. The results indicate that students perceive ChatGPT as an accessible, flexible, and personalized learning partner, supporting learning outside the classroom and creating a low-anxiety learning environment. ChatGPT was deemed effective in improving reading and writing skills through providing linguistic clarification and cognitive support. Furthermore, its use contributed to increased learning autonomy and academic self-confidence. However, students also expressed critical awareness of ChatGPT's limitations, particularly regarding response accuracy and its limited role in supporting speaking skills. Overall, ChatGPT is viewed as a complementary learning partner that supports, but does not replace, conventional English language instruction.